2019
DOI: 10.1159/000505264
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Insulin-Like Growth Factor 1 and AMD3100 Improves Motor Outcome in a Murine Model of Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Stem cell transplantation is a promising intervention for neonatal hypoxic-ischemic encephalopathy (HIE); however, universal feasibility and safety have not been thoroughly evaluated. AMD3100 and insulin-like growth factor 1 (IGF1) mobilize progenitor cells into peripheral circulation. The objective of this study was to assess the short-term efficacy of inducing endogenous stem cell mobilization after injury in a model of neonatal HIE. Postnatal day 9 CD1 pups received sham surgery or unilateral carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…2 b, c). Although a single research group [ 42 ] studied the identified proteins, this is a promising target, since Insulin-like growth factor 1 (IGF-1) has already been tested as a therapeutic approach, exhibiting good outcomes in a rat HIE model [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 b, c). Although a single research group [ 42 ] studied the identified proteins, this is a promising target, since Insulin-like growth factor 1 (IGF-1) has already been tested as a therapeutic approach, exhibiting good outcomes in a rat HIE model [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, therapeutic impact on motor function was only seen when applying a combination treatment with insulin-like growth factor 1. 54 Another strategy deserving further investigation is the pharmacological combination of AMD3100 with cobalt chloride or β3 adrenergic agonists in order to increase the mobilization of mesenchymal stromal cells from BM, 55,56 a cell population with a promising protective role in HIE. 1 Thus, it may be assumed that the subacute treatment with AMD3100 alone, despite clear evidence for therapeutic benefits in other forms of adult hypoxic-ischemic brain injury, may not be ideally suited for the treatment of HIE for so far unknown reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of AMD3100, a CXCR4 antagonist, in the subacute phase of HIE has been investigated as a possible treatment for HIE, given its ability to mobilize hematopoietic stem cells/progenitors from the bone marrow. However, this therapy provided no benefits in hypoxic‐ischemic rats and mice, and it was not shown whether AMD3100 had any impact on monocyte infiltration 99,100 …”
Section: Monocytes and Macrophages In The Developing Central Nervous ...mentioning
confidence: 99%
“…However, this therapy provided no benefits in hypoxic-ischemic rats and mice, and it was not shown whether AMD3100 had any impact on monocyte infiltration. 99,100 CD36, a type B scavenger receptor expressed in microglia/macrophages, monocytes, and other cell types, has been shown to regulate the recruitment of myelomonocytic into the CNS after NAIS. CD36 KO mice exhibited fewer classical monocytes, nonclassical monocytes, and neutrophils in the ipsilateral choroid plexus early after reperfusion, in comparison with wildtype mice.…”
Section: Mechanisms Of Monocyte Infiltrationmentioning
confidence: 99%